Mediterranean Long Shelf-Life Landraces: An Untapped Genetic Resource for Tomato Improvement - Conesa, Miquel À.; Fullana-Pericàs, Mateu; Granell, Antonio; Galmés, Jeroni (Frontiers in Plant Science, 2020)
The Mediterranean long shelf-life (LSL) tomatoes are a group of landraces with a fruit remaining sound up to 6-12 months after harvest. Most have been selected under semi-arid Mediterranean summer conditions with poor irrigation or rain-fed and thus, are drought tolerant. Besides the convergence in the latter traits, local selection criteria have been very variable, leading to a wide variation in fruit morphology and quality traits. The different soil characteristics and agricultural management techniques across the Mediterranean denote also a wide range of plant adaptive traits to different conditions. Despite the notorious traits for fruit quality and environment adaptation, the LSL landraces have been poorly exploited in tomato breeding programs, which rely basically on wild tomato species. In this review, we describe most of the information currently available for Mediterranean LSL landraces in order to highlight the importance of this genetic resource. We focus on the origin and diversity, the main selective traits, and the determinants of the extended fruit shelf-life and the drought tolerance. Altogether, the Mediterranean LSL landraces are a very valuable heritage to be revalued, since constitutes an alternative source to improve fruit quality and shelf-life in tomato, and to breed for more resilient cultivars under the predicted climate change conditions.